2006
DOI: 10.1111/j.1478-3231.2006.01245.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between oxidative stress levels and activation state on a hepatic stellate cell line

Abstract: The differences in physiological functions of stellate cell phenotypes suggest a relationship between oxidative stress levels and activation state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 46 publications
2
24
0
1
Order By: Relevance
“…The experimental model of the permanent cell line, GRX, is known to be converted to quiescent-like HSC cells when treated with indomethacin or retinol for 7 days, decreasing proliferation and extracellular matrix production, accumulating neutral lipids and retinyl esters in perinuclear lipids droplet, reducing activation markers, modifying the extracellular matrix production, reorganizing the cytoskeleton and reprogramming the metabolism (Margis and Borojevic, 1989;Margis et al, 1992;Vicente et al, 1997Vicente et al, , 1998Guma et al, 2001;Mermelstein et al, 2001;Andrade et al, 2003;Guimaraes et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The experimental model of the permanent cell line, GRX, is known to be converted to quiescent-like HSC cells when treated with indomethacin or retinol for 7 days, decreasing proliferation and extracellular matrix production, accumulating neutral lipids and retinyl esters in perinuclear lipids droplet, reducing activation markers, modifying the extracellular matrix production, reorganizing the cytoskeleton and reprogramming the metabolism (Margis and Borojevic, 1989;Margis et al, 1992;Vicente et al, 1997Vicente et al, , 1998Guma et al, 2001;Mermelstein et al, 2001;Andrade et al, 2003;Guimaraes et al, 2006).…”
Section: Discussionmentioning
confidence: 97%
“…All results were analyzed by the 2 − ΔΔCT method (Livak and Schmittgen, 2001). β-actin was used as the internal control gene for all relative expression calculations (Guimaraes et al, 2006). The real-time PCR products were separated by 2.0% agarose gel electrophoresis and visualized by ethidium bromide staining.…”
Section: Protein Determinationmentioning
confidence: 99%
“…Reactive oxygen species were measured as previously described (Guimaraes et al, 2006) with minor modifications. Briefly, peritoneal or RAW 264.7 macrophages in 24-well plates were incubated with the treatments and in the last 30 min of treatment 2′,7′-dichlorofluorescein diacetate (DCFH-DA) (10 μM) was added and incubated in the dark at 37°C.…”
Section: Ros Measurementmentioning
confidence: 99%
“…Studies have shown that HSCs are directly involved in the process of fibrosis formation and that their activation is influenced by products generated from lipid peroxidation (LPO), formation of reactive oxygen species (ROS), and presence of inflammatory mediators such as tumor necrosis factor-alpha (TNF-α), inducible nitric oxide synthase (iNOS), interleukins, and nuclear factor-kappa B[4,6]. …”
Section: Introductionmentioning
confidence: 99%